2019
DOI: 10.1002/chem.201806178
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid Stabilized Niobium Oxoclusters Catalyzing Oxidation of Sulfides with Exceptional Activity

Abstract: We present here a new class of niobium oxoclusters that are stabilized effectively by carboxylate ionic liquids. These functionalized ILs are designated as [TBA][LA], [TBA][PA], and [TBA][HPA] in this work, in which TBA represents tetrabutylammonium and LA, PA, and HPA refer to lactate, propionate, 3‐hydroxypropionate anions, respectively. The as‐synthesized Nb oxoclusters have been characterized by use of elemental analysis, NMR, IR, XRD, TGA, HRTEM. It was found that [TBA][LA]‐stabilized Nb oxoclusters (Nb−O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…The molten organic salt-stabilized Nb oxo-clusters were achieved in a similar method as previously reported by our group. 58 Briefly, niobic acid was dissolved in hydrogen peroxide, the organic salts (such as TBAF, TBACl, TBABr, TBAHSO 4 , and TBAOAc) were added to the clear solution, respectively, and then the mixture was evaporated and dried to obtain the catalyst named Nb-OC@OS-n (OS represents different organic salts and n denotes the molar ratio of organic salt to Nb atom). The components of the oxo-cluster catalysts were analyzed by elemental analysis and inductively coupled plasma atomic emission spectroscopy (ICP-AES).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molten organic salt-stabilized Nb oxo-clusters were achieved in a similar method as previously reported by our group. 58 Briefly, niobic acid was dissolved in hydrogen peroxide, the organic salts (such as TBAF, TBACl, TBABr, TBAHSO 4 , and TBAOAc) were added to the clear solution, respectively, and then the mixture was evaporated and dried to obtain the catalyst named Nb-OC@OS-n (OS represents different organic salts and n denotes the molar ratio of organic salt to Nb atom). The components of the oxo-cluster catalysts were analyzed by elemental analysis and inductively coupled plasma atomic emission spectroscopy (ICP-AES).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In our previous work, we synthesized a niobium oxo-cluster stabilized by the ionic liquid tetrabutylammonium lactate. 58 Even if the Nb oxo-cluster was used for the oxidation of various thioethers at the ppm level, it showed exceptionally high catalytic activity. As a continuation of our efforts to design an easily accessible, highly active, and stable Nb oxo-cluster for oxidation catalysis, we report herein that the commercially available molten organic salts like tetraethylammonium fluoride (TEAF), tetrabutylammonium fluoride (TBAF), tetrabutylammonium chloride (TBACl), tetrabutylammonium acetate (TBAOAc), etc.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Zhou et al . prepared a new class of IL-stabilized Nb oxoclusters by coordination stabilization with carboxylate ionic liquids and studied their catalytic performances in the selective oxidation of sulfides with H 2 O 2 in CH 3 OH solvent ( Zhou et al, 2019 ). It was found that the ionic liquid tetrabutylammonium lactate [(TBA)(LA)]-stabilized Nb oxoclusters [Nb-OC@(TBA)(LA)] were uniformly dispersed with an average particle size of 2–3 nm and could efficiently catalyze the selective oxidation, and a number of sulfides could be efficiently converted into the corresponding sulfoxides or sulfones by adjusting the equivalent of H 2 O 2 , reaction time, and reaction temperature.…”
Section: Oxidation Of Sulfides To Sulfones or Sulfoxidesmentioning
confidence: 99%
“…SCHEME 4 | Reaction route for selective oxidation of sulfides with the Nb oxocluster catalyst(Zhou et al, 2019).…”
mentioning
confidence: 99%
“…The transformation of sulfides to the corresponding sulfoxides is a significant issue for economic and environmental considerations, not only because such processes can synthesize intermediates with pharmaceutical and chemical activity but also because the transformation can purify toxic chemicals, such as oxidative detoxification of the sulfur mustard simulant and oxidative desulfurization of petroleum . Although many traditional stoichiometric oxidants (e.g., nitric acid, hypervalent iodine, oxone, K 2 FeO 4 , and so forth) have been proved to be effective for the oxidation of sulfide, most systems usually suffer from numerous defects in terms of low sulfoxide selectivity, extreme reaction conditions, complex handling procedures, as well as generating environmentally harmful toxic pollutants. As an alternative solution, therefore, a wide variety of catalytic oxidation systems using metal–organic frameworks (MOFs), ionic liquid, covalent–organic frameworks (COFs), or modified zeolites as catalysts, and molecular oxygen, hydrogen peroxide, or tert -butyl hydroperoxide as environmentally benign oxidants have gradually attracted extensive attention from researchers. Nevertheless, it is frustrating that some above systems remain displaying low sulfoxide yield and lack versatility and economic applicability. Hereto, the search for highly active and selective catalysts for the oxidation of sulfides is a challenging subject.…”
Section: Introductionmentioning
confidence: 99%